Women in the introductions poetry Farazdaq Read a poem of praise - Mahmoud Al - Rubaie, Taxrid A. (Humanities Journal of University of Zakho, 2013)
Farazdaku nique phenomenon of Arabic poetry rarely find his counterpart, enveloped in their own personal iddah , Alhmokh vigor and pride, pride. Grew dear life dignified, well-known family of prestige since the era of pre-Islam. His tribe was first class in his life and his poetry .The women gained a privileged position when Farazdak was employed by the creations of poetry as a beautiful picture prettify by his poet embody in an interview with an independent and sometimes part of the poem, so it would've read in the introductions to praise, the poem that tried Farazdak be committed in some of them the Spirit Arabians represented in this traditional style, these introductions to the limit - mostly - , their diversity between the Kin, , ruins, and An older ,young people, described the spectrum taken from the women's title and its cause.Through these introductions, we can identify the underlying emotions in the same Farazdak , observe its manifestations in the picture symbol for women to sing their hopes , passion and put them all what it feels like it and simmered in the chest . The research has been the most important results, including, Find all through the perspective of a researcher in the analysis of introductions, the purpose and linked to the president - praise - as a meaningful poems to the personal benefit of the aims of the poet behind the pursuit to satisfy acclaimed, and social expressing thoughts or feelings mean in particular. Colorful images of women at Farazdak is a symbol of life , love, art and a means for expressing emotional truth. Women in spinning (self image), in Remaining relics (nostalgia to the past), in the spectrum (the renewal of life and its continuation), An older ,young people (heartbreak and pain). And a last resort when women Farazdak imagined poetic, and Dramatic with a strong motivation positive towards creativity and excellence.